ISLAM NUSANTARA : HISTORY, DEVELOPMENT, AND CULTURAL ACCULTURATION - Citra Lestari; Nurzena Nurzena (Makkah: Journal Of Islamic Studies, 2026)
Islam Nusantara represents a manifestation of a peaceful, adaptive, and sustainable process of acculturation between Islamic teachings and local wisdom in Indonesia. This article aims to analyze the history of Islamic dissemination, the mechanisms of cultural acculturation, and the effectiveness of cultural da'wah media in shaping a moderate Islamic identity. Employing a qualitative library research method, this study synthesizes 23 scholarly sources to examine how Islamization occurred without military confrontation, but rather through networks of Islamic scholars, trade routes, and symbolic transformations within artistic media such as shadow puppetry (wayang kulit) and local architecture. The findings indicate that accommodative cultural da'wah strategies have successfully integrated the values of tawhid into local traditions without eliminating their original cultural identities. This process has given rise to an inclusive, tolerant, and civilized expression of Islam. Amid the challenges of globalization and contemporary religious moderation, Islam Nusantara has proven to be an effective strategic paradigm for maintaining social harmony, safeguarding Muslim families from value disruption, and strengthening national solidarity within a diverse ethnic landscape. By promoting the principle of rahmatan lil-'alamin (mercy to all creation), Islam Nusantara positions itself as a safeguard against radicalism while simultaneously serving as a contextual model of religiosity for modern society.